Impact of Bean Research in Rwanda and Uganda - CGIAR Standing Panel on Impact Assessment (CGIAR Standing Panel on Impact Assessment, 2014)
This Impact Brief (No 46) is based on the study that documents the impacts of improved common bean varieties on field-level yields, costs of production, and household farm incomes among smallholders in Rwanda and Uganda. Effects are also examined so that the number of people escaping poverty due to the diffusion of improved varieties can be calculated. The full report will be published shortly on this site along with the SPIA foreword.